Existence, uniqueness and some comparative statics for ratio- and Lindahl equilibria: new wine in old bottles - Wolfgang Buchholz; Richard Cornes; Wolfgang Peters (Center for Economic Studies and ifo Institute (CESifo), 2006)
We present a rigorous, yet elementary, demonstration of the existence of a unique Lindahl equilibrium under the assumptions that characterize the standard n-player public good model. Indeed, our approach, which exploits the aggregative structure of the public good model, lends itself to a transparent geometric representation. Moreover, it can handle the more general concept of the cost-share or ratio equilibrium. Finally, we indicate how it may be exploited to facilitate comparative static analysis of Lindahl and cost share equilibria.
Keywords: H41; 330